The Effect of Using Interactive Multimedia Based on Cognitive Conflict-Based Learning on Global Warming Material on Student Retention - Nahdhah Muhdia; Fatni Mufit (Jurnal Penelitian Pembelajaran Fisika, 2025)
The aim of learning physics is that students understand the learning concept before moving on to the next material. Physics learning is conditional in that concepts are mutually continuous so students must understand the material before continuing to the next material. In fact, in the field, students still experience conceptual misunderstandings in global warming material. The way out to overcome this is the use of interactive multimedia based on cognitive conflict to correct students' misconceptions and make them last longer in students' memories. The aim of this research is to see the effect of using interactive multimedia based on cognitive conflict on student retention. This research was conducted using a quasi-experimental design or quasi-experimental method. This research design uses a nonequivalent control group design, with two sample classes, namely the experimental class and the control class, each consisting of 28 students. The research instrument was 25 concept test questions about global warming material, with data collection through pretest, posttest and retest. The hypothesis analysis technique uses the Mann-Whitney test. The results indicate that students in the experimental class had higher retention compared to those in the control class. Although both groups experienced a decline in memory, the decrease was less significant in the experimental class. The hypothesis test yielded a result of 0,11 at a 0.05 significance level, confirming a significant impact of interactive multimedia based on cognitive conflict on student retention in the global warming topic. Therefore, in can be conclude that this learning approach effectively enhances student retention.